Conspiracy or Punishment? Theories on the Origins of Plague in Europe and Their Reception in Lithuania - Skujytė - Razmienė, Asta; Kontrimė, Milda (Tautosakos darbai, 2020)
A huge epidemic broke out among the armies of the Mongol prince who laid siege of the city of Caffa in 1346. Until 1350, its spread across the Western Europe erased about one third of its population. The plague caused by the yersinia pestis bacteria repeatedly broke out in Europe until the end of the 18th century. Its high rate of morbidity and mortality induced people to deliberate upon the causes of its appearance and almost regular outbreaks. The authors of the article discuss two popular European theories of the origins of plague. The first one associated the plague with the Jewish community, while the second one proclaimed it a divine punishment for the people’s sins. By means of discussing and comparing historical materials, folklore, religious literature, foreign and Lithuanian research contributions, and published sources, the authors aim to find out whether these two theories of the origins of plague could be detected in Lithuania.Various cultures tend to find different explanations for the causes of the disease; however, against the background of an epidemic, these explanations are bound to incorporate the supernatural, and interpretations of the omens (anomalous signs): e.g., an unusually bright star, a passing comet, the Northern Lights, or the like. Lithuanians also believed that sighting certain phenomena in the sky (fiery lions, a cross, militant knights, a black coffin, a star with a tail, etc.) could predict the imminent war, disease (especially plague), and other misfortunes. A popular belief also maintained that diseases (especially epidemics) could be induced by a certain order of planets; this was associated with the humoural theory existing until as late as the 19th century. Miasmic theory that grew popular in the Middle Ages asserted that people could fell ill because of the polluted air, usually blaming such pollution on the rotting and stinking organic materials. Despite growing suspicions that people themselves could contribute to the spreading of the disease (especially sailors, travelers, and persons escaping from the already affected territories), as often as not the communities resorted to scapegoating, blaming the ethnic or religious minorities, especially the Jews. The latter were accused of poisoning the food, the sources of water, or even the door handles, thus causing the plague in 1348–1351. This resulted in Jewish persecution and mass murdering in many European countries – sometimes virtually entire Jewish communities were erased.The Jewish “confessions” were usually elicited by means of torture, while “evidence” was obtained by means of searching their homes. Anything could pass for evidence, especially some suspicious cures, like theriacs – herbal mixtures particularly popular during the Middle Ages. A common belief also held the Jews to be immune to the epidemic. This rumor being particularly tenacious, the Pope Clemens VI was obliged to issue a bull in order to stop the Jewish persecution and massacre. The Pope reminded his congregation that the Jews were also affected by the plague; besides, this disease could spread in the regions where there were no Jewish inhabitants. According to some researchers, in certain countries the mortality rate among the Jewish communities could indeed potentially be lower in comparison to the general urban population – due to their nutrition peculiarities and special attention to the personal hygiene. However, these were exceptional cases, while the most recent investigations show that the Jewish communities were affected by the plague similarly to the rest of the population.In Lithuanian folklore, only meager reflections of the “poisoning Jews” theory could be found. Despite the popular stereotypes regarding the Jews that existed in the Grand Duchy of Lithuania in the course of the 14th – 18th centuries, the accusations of them causing the plague and / or spreading the disease were not particularly common. While according to the Lithuanian folklore, Jews could be associated with various illnesses, the Jewish pogroms seem to have been caused mainly by economical reasons, as well as the pan-European accusation of ritual Christian killings.Another popular theory of the origins of plague tended to regard the disaster that befell people as the divine punishment for human sins. Assorted forms of repentance were practiced in the course of the epidemic, including holding of the Mass and public flagellations. According to the 18th century sources, the Lithuanians also practiced Mass as the means of preventing the plague, which was depicted in the religious hymns as the divine wrath. The congregation would address their prayers primarily to the sacred mediators – the Virgin Mary or the so-called “plague saints” (Saint Roch, Saint Sebastian, and Saint Rosalia). In Lithuania, like elsewhere in Europe, the notion of the epidemic plague being the punishment from God or Christ was established in the church hymns, sermons, and the religious art. However, this notion does not prevail in folk culture; there, folkloric personifications of plague or its associations with other mythical beings are much more numerous. Therefore, it is reasonable to assert that at least among the peasants the image of the punishing God and plague as means of this punishment was considerably weaker than in the urban environment.As result of this research, it is evident that in Lithuania, the reception of the European theories of plague (either blaming the epidemic on the Jews or associating the disease with the divine punishment) is rather complicated. We could presume that the theory of the Jews as spreaders of the plague could be familiar in Lithuania both in the Middle Ages and subsequently; however, its reflections in folklore are rather meagre, while primary historical sources could not be obtained so far. Meanwhile the second theory maintaining the plague to be the divine punishment was established in Lithuania, as elsewhere in Europe, through the efforts of the Church (hymns, sermons, and religious art). However, the folklore data enables asserting that – at least in the peasant culture – this theory encountered considerable resistance from the established folk notion and imagery of the contagious / epidemic diseases.
Keywords: divine punishment; disease; plague; folklore; the Middle Ages; the Jews